DEVELOPING THE LEARNING SET FOR THE TOPIC OF PYTHAGOREAN THEOREM USING PROBLEM SOLVING APPROACH REFERS TO THE LEARNING TRAJECTORY WITH PROBLEM SOLVING STUDENT’S ABILITY ORIENTATION - Afifah Nur Indah Sari; Ariyadi Wijaya (Universitas Negeri Yogyakarta, 2017)
This study aims to produce learning set that includes Lesson Plan and Student Worksheet for the topic of Pythagorean theorem which are valid, practical and effective. Learning set that are developed using problem solving approach refers to the learning trajectory with problem solving ability oriented to junior high school students of class VIII. Type of the research was research and development with ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. This research paradigm is mixed method research by using embedded mixed method design. The instruments used in this research were validation sheets for measuring the validity of the learning set, student’s and teacher’s questionnaire for measuring the practicality, and test to measure the effectiveness of learning set. The results of this research are lesson plan and student worksheets using problem solving approach refers to the learning trajectory. Based on the results of validation assessment, the lesson plan was very valid with a score of 4,24 on a scale 5. While validation assessment of student worksheets obtained a score of 4,15 on a scale 5 with “valid” category. Based on practicality assessment results of student’s questionnaire obtained a score of 3,01 on a scale 4 with “practical” category and teacher’s questionnaire obtained a score of 3,45 on a scale 4 with “very practical” category. Effectiveness assesment using test obtained the level of completeness is 84.34%. Then, the average test score of the class obtained of 81.81 which indicates greater than minimum accomplishment criteria i.e. 75. So that, the learning set is effective.Keyword: learning set, problem solving, learning trajectory